2020
DOI: 10.1002/cncr.32859
|View full text |Cite
|
Sign up to set email alerts
|

Mammography screening reduces rates of advanced and fatal breast cancers: Results in 549,091 women

Abstract: Background It is of paramount importance to evaluate the impact of participation in organized mammography service screening independently from changes in breast cancer treatment. This can be done by measuring the incidence of fatal breast cancer, which is based on the date of diagnosis and not on the date of death. Methods Among 549,091 women, covering approximately 30% of the Swedish screening‐eligible population, the authors calculated the incidence rates of 2473 breast cancers that were fatal within 10 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
148
2
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 227 publications
(164 citation statements)
references
References 15 publications
6
148
2
8
Order By: Relevance
“…A recent study declared that regular mammography screening reduces the risk of breast cancer by 14%-29%. 12 Likewise, Duffy, et al, 32 reported that the mortality rate of breast cancer for women attended mammography screening within 10 years decreased by 41%. The rate of mammography for women in the present study over 40 was approximately 33%.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study declared that regular mammography screening reduces the risk of breast cancer by 14%-29%. 12 Likewise, Duffy, et al, 32 reported that the mortality rate of breast cancer for women attended mammography screening within 10 years decreased by 41%. The rate of mammography for women in the present study over 40 was approximately 33%.…”
Section: Discussionmentioning
confidence: 99%
“…Even early breast cancer can be a fatal disease if left untreated, so adequate surgery combined with appropriate perioperative therapies is essential to improve the outcome [ 9 , 10 ]. It is well known that early detection contributes to a decrease in specific breast cancer mortality [ 13 15 ], and breast cancer outcomes are dependent on timely and high-quality multidisciplinary interventions [ 14 ]. A short delay (e.g., 6–12 weeks) should not affect overall outcomes [ 9 , 10 ], while a diagnostic delay longer than 3 months potentially does [ 9 , 10 ].…”
Section: Priority Categories and Suggested Practicementioning
confidence: 99%
“…Despite improvements in therapy, breast cancer remains the leading cause of cancer-related mortality among women worldwide, accounting for approximately 600,000 deaths annually (1). Randomised trials and incidence-based mortality studies have demonstrated that population-based screening programmes substantially reduce breast cancer mortality (2)(3)(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%